Produção de mudas de cafeeiros sob efeitos de lâminas de irrigação, hidrorretentor e recipientes - Azevedo, José Maria Gonçalves de (2012)
The coffee seedling quality is of fundamental importance in the success of a crop field. Therefore, the objective of this study was to analyze the quality of Coffea canephora Pierre ex Froehner seedling, variety Robusta Tropical (EMCAPER 8151 Robusta Tr